An exploratory study on the perception of the over-the-top (OTT) industry among film and media production major university students: Utilizing the Q methodology - Kang Suk Lee; Song Yi Lee (PLoS ONE, 2025)
This study investigates the perceptions of university students majoring in film and media production (FMP) regarding the over-the-top (OTT) industry. We used the Q methodology to achieve this study’s purpose, with 33 Q sets and 22 university students majoring in FMP. The study revealed three perception structures of FMP major university students regarding the OTT industry. Type 1 considered the diversity and accessibility of OTT to be important from the consumer’s perspective, and Type 2 emphasized the importance of improving the quality of content from the producer’s perspective. Even though Type 3 considered the OTT industry an excellent platform, they tended to think of movies in theaters as the final destination. Based on the study’s results, all types thought that the growth and development of the OTT industry would continue. However, the study demonstrated that they need perceptions from a macroscopic viewpoint in areas related to OTT industry technology, education, and systems.